External Auditors' Perception of Cloud Computing Use in Indonesia : A Study of Non-Big Four CPA Firm in Bali - Bevi Libraeni; Mila Rosa Desmayani (Jurnal Ekonomi Manajemen Bisnis dan Akuntansi, 2025)
This study explores how cloud computing services enhance audit performance from the perspective of external auditors, focusing on factors influencing adoption among non-Big Four public accounting firms (PAFs). Employing a qualitative approach with an interpretive paradigm, data were collected through in-depth interviews and document analysis. A total of eight external auditors from non-Big Four PAFs in Bali participated in the study. The findings reveal that auditors perceive cloud computing as beneficial due to its ease of access, system reliability, enhanced information sharing, and improved data security. One participant stated, "Cloud platforms help us review client documents remotely and in real-time, which reduces delays in the audit process." Despite these advantages, concerns remain regarding data confidentiality and dependence on internet connectivity. The dominant theoretical lens guiding the analysis is the Technology-Organization-Environment (TOE) framework, supported by elements from the Technology Acceptance Model (TAM) and Institutional Theory. Practically, this study contributes by offering insights into how smaller firms can strategically adopt cloud technology to improve audit efficiency and competitiveness, while addressing institutional and organizational readiness.